Aplicação das ferramentas de gestão da qualidade para a redução de paradas e quebras prematuras de equipamentos utilizados para fabricação de correias transportadoras - DIAS JÚNIOR, Flávio da Silva (2022)
Industries in Brazil show a growing increase in production in the year 2022, especially the mining sector in the north and northeast. With this sector on the rise, the demand for conveyor belts also increases, due to the large extensions of mines, which makes it necessary to use conveyor belts to carry out the transport of ore, since it reduces costs and increases productivity. Therefore, a case study was carried out in a company that manufactures conveyor belts, which has an average production capacity of 430 tons of rubber per month and operates 23 hours a day, which requires the maximum amount of equipment. With the objective of increasing production capacity and decreasing downtime and equipment breakage rates, Quality Management tools were used. Firstly, it was necessary to apply the Pareto chart to identify the area most affected by maintenance shutdowns. Secondly, maintenance indicators were calculated (Reliability, availability and maintainability), and finally, an analysis of the five whys for each failure was carried out, to reach the root cause and brainstorming to define a strategy and action plan. to troubleshoot. With these tools, it was possible to analyze and apply improvements in the rubber processing process for the manufacture of conveyor belts, and then compare the results for the period from August to December of the year 2021, with the period from January to May of the year 2022, after improvement, indicating a decrease in the number of stops for corrective maintenance, an increase in equipment reliability and an increase in the quality of the conveyor belts produced.